catena-Poly[[[tetraaquacopper(II)]-μ-4,4′-bipyridyl-κ(2) N:N′] tetrafluoridosuccinate tetrahydrate] - Yu, Guo-Jun (International Union of Crystallography, 2012)
In the title compound, {[Cu(C(10)H(8)N(2))(H(2)O)(4)](C(4)F(4)O(4))·4H(2)O}(n), the Cu(II) atom adopts an elongated octahedral geometry because of the Jahn–Teller effect. Both cation and anion have crystallographic twofold rotation symmetry with the twofold axes passing through the Cu and N atoms and through the midpoint of the central C—C bond. The 4,4′-bipyridyl ligand links the Cu(II) atoms into a linear chain along the b axis. O—H⋯O hydrogen-bonding interactions between the cationic chains and the tetrafluoridosuccinate anions and the free water molecules generate a three-dimensional supramolecular network.